Die gereform eerde skrifbeskouing en moderne metodes van verklaring van die nuwe testament - Botha, J. (Koers, 1986)
In this article aspects of current exegetical methodology in New Testament studies are evaluated with reference to the reformed doctrine of Holy Scripture. The main aspects of the reformed doctrine of Scripture are discussed. Certain textual-theoretical principles which form the basis of the new methodologies in New Testamant studies are discussed, as well as the most important methodological principle in a textual-theoretical approach and the determining factor of one's concept of the text as such.